The impact of Virtual Reality (VR) therapy and its modifications in mental health nursing services: A scoping review - Budiman , Amin Aji; Megananda, Nadya Karlina; Faradisa, Elok (PT Saintek Medika Nusantara, 2022)
The development of technology to improve effective, efficient, and comprehensive mental health care services have now been carried out, one of which is the development of Virtual Reality Therapy (VR) in mental health services to achieve optimal health by creating the illusion of living in virtual reality. This article aimed to find out the application of technology-based Virtual Reality Therapy (VR) in mental health care services and modifications that might be made by reviewing the existing limitations. A scoping review was written based on identifying scientific articles in three databases, namely Science Direct, Pubmed NCBI, and Proquest, using the terms Virtual Reality Therapy, Mental Health, and Nursing. The author carried out the selection and analysis process using PRISMA based on the inclusion and exclusion criteria determined by the researcher, and a total of 15 articles were analyzed. The use of technology-based Virtual Reality Therapy in psychiatric nursing has been shown to have a positive impact on the condition of psychological health problems, including reducing anxiety, changing moods, emotions, empathy, reducing stress, loneliness. Therapy delivery system and allows for program modifications. Virtual Reality Therapy has a positive impact on improving one's mental health. It is necessary to develop modifications in VR implementation to achieve optimal physical and psychological health